Las Ciencias Humanas y el Paso de la Filogenia a la Ontogénesis - Lastra B., Rosalía S.; Albuquerque, Ayuzabet de la Rosa (Acta Universitaria, 2006)
This report is a summary of research carried out as part of the Human Sciences course taught by Prof. Alain Chanlat, of the Université de Montréal (HEC), in the Doctorate program in Organizational Studies, under the aegis of UAM Iztapalapa. Its objective is “to try to answer, from an interdisciplinary standpoint, the question: What is man? We try to establish the basic principles of human sciences necessary for an understanding of who we are as a species (phylogenical perspective) as well as unique individuals (ontogenical perspective). This double perspective allows us to present, in sequence, the biological, neurological, linguistic, psychological and social dimensions of the human being, and the ways in which these dimensions interact.” The content is a synthesis of the principal postulates and related ideas corresponding to the works of the authors that have been consulted, each of which represents its own contribution to the answer being sought. The ultimate goal is to provide the reader with reasons for reading these authors’ complete works; supporting this synthesis through brief critical formulations and proposals.
Keywords: Array; Array; Array; Array; Array